Financial performance analysis of Mutual Trust Bank PLC: a study on performance analysis of Mutual Trust Bank PLC - Zohra, Fatematuz (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, 2024.